MODEL PENINGKATAN PARTISIPASI BELAJAR MELALUI PENERAPAN STRATEGIISICARD-MATCH DALAM PROSES PEMBELAJARAN PENDIDIKANKEWARGANEGARAAN PADA SISWA KELAS VIII-H SMPMUHAMMADIYAH 7 SURAKARTA TAHUNPELAJARAN 2015/2016 - NURKAYATI, SITI; , Drs. Sutan Syahrir Zabda, SH,MH (2016)
This action research is aimed to improve learning participation in learning process of Citizenship Education in the VIII-H grade students of SMP Muhammadiyah 7 urakarta through the implementation of ISICARD-MATCH strategies. The participation of students before doing the research only 4 childrens or 21,05% of the 19 students in high level. The subject of this research is all students in VIII-H grade of SMP Muhammadiyah 7 Surakarta. The data of the research from informan and place, where were obtained learning activities was happening. In this research, echnique of collecting dataa using observation and interview methods. The test validity of the data by triangulation of data sources and data collection techniques or methods. Analysis of the data by applying the model of flow (flow models of analysis) through data collection, data reduction, data presentation, and conclusion. The results of this study shows that after testing the model through the implementation of ISICARD-MATCH strategies, in model test I students who have studied a relatively high participation of as many as 13 children, or 68.42% of the 19 learners. Cycle II students' learning participation is increasing to 16 children, or 84.22% of the 19 learners. Based on the result of the data test model, then the application of SICARD-MATCH strategies can participation improve in the learning process of learning Citizenship Education in VIII-H grade students of SMP Muhammadiyah 7 Surakarta in academic year 2015/2016.